The Impact of Macro-Economic GDP on Firm Level Earnings Management in Egypt - Mahmoud, Nevin Hussein Mohamed; Elewa, May M.; Mahmoud Abdel aal, Yasmin Abdel aal (Journal of Accounting Research, Organization and Economics, 2024)
Objective This paper aims to examine whether and how macro-economic gross domestic product GDP affects earnings management EM (represented by real earnings management REM and accrual-based earnings management AEM) at firm level.Methodology The study collected numerical data from the International Monetary Fund IMF the Central Bank of Egypt, the World Bank, as well as financial statements of 40 listed non-financial firms from the EGX 100. Data is collected for 5 years corresponding to 200 firm-year observations during 2018-2022. The study applies the panel data method. The designated sample of firms are listed on the EGX 100, have yearly financial statements, have not discontinued during the study period, run in cash, the currency is recorded in the Egyptian Pound EGP, and have complete data.Results The overall actual result of this analysis of the macro-economic GDP on firm level EM variables of listed Egyptian nonfinancial institutions indicate there is no relationship among the GDP (X), REM (Y1), and AEM (Y2) whatsoever. While the result of this study is contrary to its predecessors yet it is an indicator for decision makers in the Egyptian business environment to reconsider the impact of macro-economic GDP variable on firm level EM variables.Novelty/Originality The result of this paper is contrary to its predecessors. Nevertheless, it is an indicator for decision makers in the Egyptian business environment to reconsider the impact of macro-economic GDP variable on firm level EM variables.